Wideband Square Loop Antenna with Parasitic Loop Component. Issue 10 (26th July 2013) - Lee, Hyeonjin; Kim, Tae‐Hong
ABSTRACT In this article, we designed the broadband square loop antenna with a parasitic loop. To increase bandwidth of the single square loop antenna, we desinged the antenna with the parasitic loop at outside of the square loop. The feeding method of the proposed antenna is fed by a coplanar waveguide structure. We analyzed and designed the antenna by using Ansoft co.' HFSS. The bandwidth of the proposed antenna with the parasitic loop was increased above 2.5 times compared with single square loop antenna. The proposed antenna has an impedance bandwidth of 2.52 GHz under the condition below voltage standing wave ratio two and a maximum gain of 8.7 dBi at the operating frequency of 6.4 GHz. The designed antenna could be used to support WLAN communications and ITS applications bands. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2302–2304, 2013